2009
DOI: 10.1073/pnas.0900693106
|View full text |Cite
|
Sign up to set email alerts
|

The assembled structure of a complete tripartite bacterial multidrug efflux pump

Abstract: Bacteria like Escherichia coli and Pseudomonas aeruginosa expel drugs via tripartite multidrug efflux pumps spanning both inner and outer membranes and the intervening periplasm. In these pumps a periplasmic adaptor protein connects a substrate-binding inner membrane transporter to an outer membrane-anchored TolC-type exit duct. High-resolution structures of all 3 components are available, but a pump model has been precluded by the incomplete adaptor structure, because of the apparent disorder of its N and C t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

11
392
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 262 publications
(406 citation statements)
references
References 40 publications
11
392
3
Order By: Relevance
“…Although the mechanism by which this substitution confers nonsusceptibility to AZM remains unclear, the results of the EB efflux assay showed that AZM addition competed with EB efflux at the early stage, suggesting that this amino acid substitution contributed to alterations in initial recognition and efflux. AcrB is known to form a trimer that acts as a complex with the outer membrane channel TolC and the membrane fusion protein AcrA (10)(11)(12). This efflux system discharges the agents from both the inner membrane and the periplasm (10).…”
mentioning
confidence: 99%
“…Although the mechanism by which this substitution confers nonsusceptibility to AZM remains unclear, the results of the EB efflux assay showed that AZM addition competed with EB efflux at the early stage, suggesting that this amino acid substitution contributed to alterations in initial recognition and efflux. AcrB is known to form a trimer that acts as a complex with the outer membrane channel TolC and the membrane fusion protein AcrA (10)(11)(12). This efflux system discharges the agents from both the inner membrane and the periplasm (10).…”
mentioning
confidence: 99%
“…1, crosssection 3) interact with the apex of AcrB (9). On disruption of the bond network, in both TolC RS and TolC YFRS , the tips undergo immediate large changes (Fig.…”
mentioning
confidence: 99%
“…The structures of all three drug efflux pump components are known: the trimeric TolC exit duct (5), the trimeric AcrB transporter (6,7), the partial adaptor AcrA (8), and the complete homologous Pseudomonas adaptor MexA (9,10). We have established a model of the assembled tripartite machinery on the basis of extensive site-specific cross-linking between the flexible, linearly arranged multidomain adaptor and its two cognate partner proteins (9,11). To recruit TolC, the 47 Å long α-hairpin domain of the adaptor packs against intramolecular grooves formed by entrance helices of each TolC protomer (9,11).…”
mentioning
confidence: 99%
See 2 more Smart Citations